Sem "IN", zdravo ŽIVIM! - Majerič, Matej (Šport (Ljubljana), 2019)
The purpose of the paper was to present an systematically designed video workouts model. According to some data, overweight is mainly related to excessive consumption of unhealthy snacks and drinks that have low nutritional and high-energy value. According to this, we selected foods that belong to this group. We prepared a model of workouts and named them after the selected foods. The energy value of a particular food corresponds to the energy consumption during a workout named after it. The intensity of them was calculated on the basis of the metabolic equivalent of task (MET). MET is the generally accepted value for determining the intensity of physical activity. The first level of exercise is low intensity (up to 3 MET), the second to fourth level is moderate (4 to 6 MET), the fifth to eighth is high (6 to 9 MET), and the ninth and tenth levels are very high (above 9 MET). In this paper, we outlined how to use a video workout model for improving physical fitness and overweight management.
Keywords: healthy lifestyle; model; overweight management; prekomerna telesna teža; sport; šport; telesna pripravljenost; vadba; video; video posnetki; workout; zdrav življenjski slog